THE ROLE OF STRUCTURAL SIMULATIONS IN DEVELOPING INNOVATIVE SAFETY CAPSULES - Mircea ENE; Ionel SIMION (Journal of Industrial Design and Engineering Graphics)
Abstract: Structural simulations play a crucial role in the development of new products, particularly in the early design phase, where insights into performance under different load conditions can significantly influence design choices. This paper explores the application of structural simulations in developing the " Emergencies Safety Capsules", an innovative housing solution, highlighting the necessity and benefits of these simulations in creating safe, reliable, and efficient designs